Microstructure of the EN-GJL-150 Cast Iron Matrix Composite with SiC and Al₂O₃ Particles - Piątkowski, J.; Wojciechowski, M.; Fusiarz, J. (Archives of Foundry Engineering, 2026)
*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(--scroll-root-safe-area-inset-bottom,0px)+var(--thread-response-height))] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:25135059-bb5b-4fbe-8621-c6dbe0fc3c4c-2" data-turn-id-container="request-WEB:25135059-bb5b-4fbe-8621-c6dbe0fc3c4c-2" data-testid="conversation-turn-6" data-turn="assistant"><div class="text-base my-auto mx-auto pb-8 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" data-conversation-screenshot-content=""> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="86899297-2a49-4d64-8826-082064b1bc28" data-turn-start-message="true" data-message-model-slug="gpt-5-6-thinking"> The paper presents an evaluation of the microstructure of a newly developed cast iron–ceramic composite intended for modern braking systems, such as brake discs or brake drums. The composite matrix is grey cast iron with flake graphite (EN-GJL-150), commonly used for brake disc production. The reinforcing phase is a porous ceramic composed of 70 wt.% SiC and 30 wt.% Al₂O₃, intended to enhance the crystallization process and facilitate graphite nucleation in the pearlitic matrix. Microstructural investigations were carried out using digital optical microscopy and scanning electron microscopy (SEM). The results show that reinforcement of the matrix with ceramic particles significantly alters the microstructure of the investigated cast iron. Microstructural analysis of the EN-GJL-150 + SiC + Al₂O₃ composite revealed a previously unreported phenomenon of nucleation occurring at the cast iron–ceramic phase boundary. Consequently, the general assumptions of Riposan’s theory concerning the role of oxide micro-inclusions and complex manganese sulphides of the (Mn,X) S type in the nucleation and crystallization of graphite precipitates were confirmed. At the same time, it was found that in the case of in situ cast iron–ceramic composites (GJL-150 + SiC + Al₂O₃), this theory should also account for the beneficial role of ceramic particles in promoting a uniform distribution of type A graphite flakes, which nucleate on the surfaces of these particles within the interfacial transition zone. Thus, the nucleation role of oxide micro-inclusions (the first stage of Riposan’s theory) could be assumed by SiC and Al₂O₃ particles (Fig. 6), which provide substrates for the heterogeneous nucleation of (Mn, X) S sulphides. The microstructure of such a composite may have a beneficial effect by reducing the wear of friction components in braking systems and decreasing environmental dust emissions from wear products, as required by new European Union regulations, e.g., the EURO 7 standard.